Cultivating the Spirit of Unity from an Early Age: Internalizing the Values of the Third Preceptions of Pancasila in Students of Elementary School - Mar’atus Sholika; Fia Alifah Putri (Yayasan Zia Salsabila, 2025)
This study investigates the integration of Artificial Intelligence (AI) in Madrasah learning to improve the quality of education. The main issue addressed is how AI-assisted learning media can help Madrasah students understand the learning material, foster creativity, and enhance communication skills. The purpose of this study is to explore the impact of AI-based media on the learning process and student learning outcomes in Madrasah. This research employs a mixed-methods approach with qualitative analysis assisted by NVivo to explore the experiences of students and teachers in using AI technology. The findings indicate that AI media significantly facilitates the understanding of learning materials, encourages student creativity, and improves their ability to communicate both verbally and non-verbally. The impact of AI media not only supports the improvement of the quality of learning but also provides a more interactive and personalized learning experience. The implications of this research show that while AI technology holds great potential, access to technological infrastructure and data security for students remain major challenges. This study recommends further research and the development of policies that support equitable access and data protection for more effective AI implementation in Madrasah.